Gender, Caste and Matchmaking in Kerala: A Rationale for Dowry - Praveena Kodoth (Development and Change 39(2): 263-283 (2008)., 2008)
The matrilineal castes of northern Kerala consider dowry demeaning and resort to it only in `exceptional' circumstances. In local discourse, dowry is transacted when women are considered `old' by the standards of the marriage market, where over-age is a condition reached usually on account of what is considered a deficit of a normative conception of femininity. Dowry is practised openly only by poor and socially vulnerable households, as the relatively affluent could mask dowry with hidden compensations. This article explores the ways in which gender mediates matchmaking and generates a residualcategory of women for whom dowry is openly negotiated. Open negotiation on the margins of the marriage market expose the terms of exchange in `respectable' society, where matchmaking strategies reveal the emphasis placed on conjugality and on caste in the social construction of women's interests and identity. Up to the mid-twentieth century, matrilineal women derived their identity from their natal families. The political economy of marriage in Kerala brought a new emphasis to bear on conjugality and on caste, which generated new restrictions on women and produced a rationale for dowry